Analisis Pola Perubahan Penggunaan Lahan Menggunakan Google Earth Engine Di Kecamatan Wawonii Barat - Padarlan Padarlan; Jamal Harimudin; Sawaludin Sawaludin; Tahir Tahir; Saban Rahim (Universitas Halu Oleo, 2024)
Konawe Island Regency was formed in 2013 as a new autonomous entity, with West Wawonii District serving as its capital. As a result, developments in the West Wawonii District have impacted agricultural and non-agricultural land use changes. The study's objectives were to determine land usage in 2011 and 2022, as well as analyze land use patterns from 2011 through 2022. The study made use of SHP Konawe Islands Regency data, BPS data for 2012 and 2022, Landsat 7 and 9 photos, and RBI maps. The Classification And Regression Tree (CART) method is used in this study, which is conducted through the Google Earth Engine. Based on the outcomes of the investigation, the following land use classes were determined for 2011 and 2022: The area of vegetation increased from 5625.36 ha to 7.970.13 ha, the area of open land decreased from 45 ha to 41.76 ha, the area of shrubs decreased from 2.799.99 ha to 1.523.97 ha, the area of mangroves increased from 204.66 ha to 206.91 ha, the area of residential land increased significantly from 58.23 ha to 261.45 ha, and the area of water bodies decreased from 133.44 ha to 126.45 ha.